Learning Alternative Energy using Graphic Video Media - Nugraha, A.A. Putu Pradana Yogi; Widiana, I Wayan; Parmiti, Desak Putu (International Journal of Elementary Education, 2021)
In online learning, teachers need media assistance in the learning process. Therefore, it was necessary to assist the development of media in the form of graphic video media. This study aimed to develop graphic video media and determine the validity of video graphic media. The data generated in this study were qualitative and quantitative. This research was development research carried out using the ADDIE model. The subjects of this study were 2 media experts, 2 design experts, 2 material experts, 1 teacher or practitioner, and 12 students. Data collection in this study used a questionnaire/questionnaire method. The data obtained were then analyzed using the Aiken validation index formula to determine the average validation of video graphic media. The development of graphic video media was declared valid with the overall Aiken validity index by the lowest expert 0.5 and the highest 1, practitioner or teacher reviews having a percentage of 98%, and overall student reviews having a percentage of 94%. Thus, graphic video media on the topic of alternative energy and its utilization that had been developed can be used as learning media to help students understand the subject matter, especially alternative energy materials and their use in online learning.